Designing the Layout of Fibreglass Production Facilities Using the ARC (Activity Relationship Chart) and ARD (Activity Relationship Diagram) Methods at PT. XYZ - Puji, Ari Andriyas; Mulyadi, Agus; Novrianto, M. Fajri (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
PT. XYZ is a plastic material and product manufacturing company founded in Riau in 1997. This company produces fibreglass (FRP) goods and accepts design requests according to consumer demand. In addition, PT. XYZ also has water tanks made of Polyethylene (HDPE) and stainless steel. In practice, some inefficiencies and inefficiencies make it difficult for operators to find tools such as grinders. This study uses the ARC (Activity Relationship Chart) and ARD (Activity Relationship Diagram) and redesigns the layout of the fibreglass production facility. The results of the study show changes and rotations in the 90º room operator, the transfer of measurements and cuts close to the base material mixture workstation located in the fibreglass production division room, and the addition of 4 workstations because it utilizes an empty floor. Keywords: ARC, ARD, Fiberglass, Layout